Idiopathic granulomatous orchitis: A case study - Miguel Armando Benavides-Huerto; Jaime García-Figueroa; Venice Chávez-Valencia; Francisco Alejandro Lagunas-Rangel (Urology Case Reports, 2024)
Idiopathic granulomatous orchitis (IGO) is a rare inflammatory disorder of unknown etiology affecting the testis. Presented here is the case of a young patient who developed IGO, potentially associated with an anti-sperm antibody-mediated autoimmune response.